Comparison of fortified, sfursat, and passito wines produced from fresh and dehydrated grapes of aromatic black cv. Moscato nero (Vitis vinifera L.). (August 2017) - Ossola, Carolina; Giacosa, Simone; Torchio, Fabrizio; Río Segade, Susana; Caudana, Alberto; Cagnasso, Enzo; Gerbi, Vincenzo; Rolle, Luca
Abstract: Moscato nero d'Acqui is an Italian aromatic black winegrape variety characterized by a low content of anthocyanins (mostly tri-substituted), a satisfactory content of high molecular mass tannins, and a fair amount of terpenes. The grapes were subjected to a postharvest dehydration process under controlled thermohygrometric conditions (16–18 °C, 55–70 RH%, 0.6 m/s air speed) with the aim to produce three different special wine types ( fortified, sfursat, and passito ) from fresh, partially dehydrated (27°Brix), and withered (36°Brix) grapes, respectively. Chemical traits of produced grapes and wines were then evaluated through spectrophotometric, HPLC, and GC–MS methods. Increased contents of skin phenolic compounds and reduced extractable contents of seed phenolic compounds were observed as dehydration progressed. Few significant differences were found in the anthocyanin profile of grapes, although the relative abundance of coumaroylated anthocyanins was higher in dehydrated grapes. The predominant free volatile compound found in grapes was geraniol, which decreased with increasing water loss, whereas the contents of major glycosylated volatile compounds increased even above the concentration effect. The changes in the phenolic composition among wines agreed with those among grape skins. Fortified wines were chromatically unsatisfactory probably due to the low content of total anthocyanins, whereas sfursat and passito wines meet good chromatic characteristics as a result of the concentration effect during grape dehydration. Fortified and sfursat wines had free aroma profiles richer in 2-phenylethanol and citronellol, whereas passito wines were mainly composed of 2-phenylethanol and 2-phenylethyl acetate, citronellol being the predominant terpenol in all the wine types studied. Graphical abstract: Highlights: Suitability of Moscato nero d'Acqui grapes to dehydration and winemaking was tested. Grape dehydration increased phenolic contents with similar anthocyanin forms ratio. Free terpene concentration decreased mainly in the first dehydration phase. Sfursat and passito wine had higher aroma richness and better color characteristics.